2018
DOI: 10.3892/ol.2018.9422
|View full text |Cite
|
Sign up to set email alerts
|

Transition of serum cytokines following pancreaticoduodenectomy: A subsidiary study of JAPAN‑PD

Abstract: Our previous study aimed to examine the effect of TJ-100, a widely used herbal medicine, on intestinal function following pancreaticoduodenectomy (PD) in a multicenter, randomized, double-blinded, placebo-controlled manner (JAPAN-PD study). This concomitant study investigated the effect of TJ-100 on serum cytokine levels in patients who underwent PD. Due to the fact that several clinical variables can affect the absolute values of baseline serum cytokine levels, the ratios of the cytokine levels on postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We have previously summarized the clinical variables of these patients. 12 The tumor characteristics, operation variables, and patient characteristics were similar between the two groups. However, the mean age of the patients was slightly higher in the TJ-100 group than that of the Placebo group (64.9±8.0 vs 65.1±11.4, p=0.004, t -test).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…We have previously summarized the clinical variables of these patients. 12 The tumor characteristics, operation variables, and patient characteristics were similar between the two groups. However, the mean age of the patients was slightly higher in the TJ-100 group than that of the Placebo group (64.9±8.0 vs 65.1±11.4, p=0.004, t -test).…”
Section: Resultsmentioning
confidence: 79%
“… 11 Nevertheless, TJ-100 regulated the serum levels of interleukin (IL)‑4, IL‑9, IL‑10, PDGF-BB, and TNF-α in patients without severe inflammation. 12 This suggests that TJ-100 exerts its effects under specific conditions that should be further studied in the future.…”
Section: Introductionmentioning
confidence: 99%
“…It can thus be speculated that proteases in pancreatic juice are likely to be activated into active forms under a high serum CRP environment. PD is known as one of the representative surgical procedures that often bring about highly inflammatory stress without infection 30 . Intra‐abdominal infection and markedly elevated CRP (which is suggestive of a highly inflammatory status) can affect each other and may form a vicious cycle to worsen the other.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding study limitation (c), elevation of CRP may be suppressed by markedly exaggerated stress, which has been reported to induce an anti‐inflammatory response 30 . A recent study that demonstrated a benefit of perioperative steroid use in patients undergoing PD showed that the use of steroid significantly reduced the highest value of CRP in the early postoperative period 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a meta‐analysis of DKT was conducted. As shown in Table 2, previous studies by RCTs and meta‐analysis on DKT have been reported [17, 20–60]. These studies are categorized according to the underlying disease and the targeted condition, and the main ones are described below.…”
Section: Clinical Applications and Clinical Trialsmentioning
confidence: 99%